2018
DOI: 10.1002/chem.201803718
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Incorporated α‐Ni(OH)2 Hierarchical Nanosheet Arrays for Electrocatalytic Urea Oxidation

Abstract: An iron-incorporated α-Ni(OH) nanosheet array catalyst characterized by hierarchical surface nanobelts and robust urea oxidation performance are reported. The unique single-crystalline belt-on-sheet hierarchical nanostructure was identified and it endows more reactive edges for the Ni -to-Ni pre-oxidation process to boost the generation of active high-valence species for the urea oxidation reaction (UOR). Benefitting from the optimal Fe concentration, the UOR activity was further optimized owing to the favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 35 publications
4
78
0
Order By: Relevance
“…The contrastive performance of Ni(OH) 2 –NiMoO x /NF for OER and UOR are exhibited in Figure e. The oxidation peaks in the curve of OER belongs to the oxidation of Ni (0), while the phenomenon that no oxidation peak emerges in the polarization curve of UOR is consistent with literature reports . To attain the current density of 50 mA cm −2 , a greatly lowered potential of 143 mV is manifested for UOR compared with pure OER.…”
Section: Methodssupporting
confidence: 86%
“…The contrastive performance of Ni(OH) 2 –NiMoO x /NF for OER and UOR are exhibited in Figure e. The oxidation peaks in the curve of OER belongs to the oxidation of Ni (0), while the phenomenon that no oxidation peak emerges in the polarization curve of UOR is consistent with literature reports . To attain the current density of 50 mA cm −2 , a greatly lowered potential of 143 mV is manifested for UOR compared with pure OER.…”
Section: Methodssupporting
confidence: 86%
“…However, urea electrolysis suffers from intrinsically sluggish kinetics owing to its 6 e − transfer process, complicated intermediates transfer, and multiple gas‐desorption steps . Previous studies showed that nickel oxides exhibited higher catalytic activity for UOR than other metals and metal oxides in alkaline media, where Ni 3+ sites were identified as the catalytic active sites . The typical reaction pathway was proposed as: *CO(NH 2 ) 2 → *CO(NH.NH 2 )→ *CO(NH.NH)→ *CO(NH.N)→ *CO(N 2 )→ *CO(OH)→ *CO(OH.OH)→ *COO, with the desorption of *COO intermediate as the rate‐determining step (RDS) .…”
Section: Figurementioning
confidence: 99%
“…Detailed structural analyses indicate that the wire‐on‐sheet nanostructure is single‐crystalline with abundant surface nanowires on the ultrathin 2D layer. Besides, by modifying the metal precursors, controllable elemental doping can be readily achieved, and the as‐obtained Cu, Fe and Ce doped catalysts exhibit remarkable performance on electro‐oxidation reactions such as OER and the urea oxidation reaction . Similarly, 2D nanosheets grown on 1D nanoarrays were also reported, for which the 1D charge transport pathway and the highly exposed surface sites could effectively boost the OER process .…”
Section: Novel Strategies For Optimizing the 2d Oer Catalystsmentioning
confidence: 99%